PERFORMANCE ANALYSIS OF SHARIA RURAL BANKS IN INDONESIA WITH THE ISLAMICITY PERFORMANCE INDEX METHOD - Jihan Indah Pitriani; Aneta Rakhmawati; Rizky Fadhillah (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2025)
This study aims to evaluate the performance of Sharia Rural Banks in Indonesia using the Islamicity Performance Index method. The research method used is descriptive qualitative with quantitative secondary data. The study population includes Sharia Rural Banks in Indonesia registered with the Financial Services Authority in 2022, with 36 samples selected through purposive sampling. Data analysis used non-statistical and descriptive quantitative methods. The results show that most have a healthy performance in the Profit Sharing Ratio (PSR) indicator, with Dinar Ashri having the highest PSR. However, the Zakat Performance Index (ZPR) shows an unhealthy predicate, with Hikmah Khazanah having the highest ZPR. The Equitable Distribution Ratio (EDR) shows that most have an unhealthy predicate in qardh, while employee expenses are mostly in a healthy predicate, and net profit is still unhealthy. Halal investment and Islamic income are rated very good, with Amanah Ummah having the highest indicator. The AAOIFI Index shows most SHARIA RURAL BANKS have a good percentage of financial statement disclosures, with Bhakti Sumekar having the highest percentage. Al Masoem was identified as the best sharia performing Sharia Rural Banks based on the Islamicity Performance Index.